Now media : the evolution of electronic communication - Medoff, Norman J.; Kaye, Barbara K (N. York Routledge, 2021)
"Now in its 4th edition, this book is one of the industry's leading texts on the evolution of electronic mass communication in the last century. Now Media, 4th edition (formerly Electronic Media) provides a synopsis of the beginnings of electronic media in broadcasting and the subsequent advancements into digital media. Each chapter is organized chronologically, starting with the electronic media of the past, then moving to the media of today, and finally, exploring the possibilities for the media of the future. Topics discussed include the rise of social media, uses of personal communication devices, the film industry, and digital advertising. Focusing on innovations that laid the groundwork for modern day television and radio and for the development of the Internet and social media, the book offers a comprehensive overview of the world of communication technology. New to the 4th edition is a chapter on virtual reality technology, as well as a discussion of the impacts of the 2020 Covid-19 pandemic on media consumption habits. This book remains a key text and trusted resource for students and scholars of digital mass communication and communications history alike. The book also features a companion website with updated instructor materials, including PowerPoint slides and test banks"--
Includes bibliographical references and index.
Keywords: Broadcasting -- History; Electronic communication; Journalism; Mass media -- History; Digital media -- History; Telecommunication -- History